Impact of Hypoglycaemia on Heart Rate in Diabetic versus Non Diabetic Patients on Haemodialysis: A Cross-sectional Study - Charan Bale; Atul Sajgure; Shreeharsh Godbole (Journal of Clinical and Diagnostic Research)
Introduction: Patients with Chronic Kidney Disease (CKD) on maintenance Haemodialysis (HD) are at risk of hypoglycaemia during HD. This is especially important in patients with diabetes mellitus. Patients with CKD are also known to have heart rate variability during HD. Aim: This study aims to study the impact of hypoglycaemia on heart rate in diabetic versus non diabetic patients undergoing maintainence HD. Materials and Methods: This was a cross-sectional study done at a tertiary care centre in Western India from July 2022 to October 2024. A total of 50 patients of CKD on maintenance HD were enrolled. They were monitored for two consecutive HD sessions, each of four hours. Participants were divided into two groups of 25 participants each- ‘diabetic group’, having patients with diabetes mellitus, and ‘non diabetic group’, comprising of patients without diabetes mellitus. Continuous blood glucose was monitored along with heart rate for the time on HD. Hypoglycaemia was checked for association with heart rate variability at the time of the hypoglycaemic episode. Results: Hypoglycaemia was seen in 7 (28%) of the diabetic group, and in 2 (8%) of non diabetic group (p= 0.0657). All hypoglycaemic episodes were asymptomatic. Patients with diabetes have a higher heart rate during a hypoglycaemic event, compared to non diabetic patients (p=0.0002). Conclusion: Hypoglycaemia was more common in patients with diabetes with CKD on HD, though not significant. This hypoglycaemia was also associated with a higher heart rate in patients with diabetes. Hypoglycaemia was also seen in patients not having diabetes mellitus. The study emphasises the importance of monitoring of blood sugar levels along with heart rate variability in patients of CKD during HD.